Mendorong Pertumbuhan UMKM dengan Menggunakan Konsep Bagi Hasil Sistem Mato - Hanif Hanif; Abdullah Rahman (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study is to encourage the use of profit sharing based on the mato system in the management of MSMEs that are adapted to the characteristics of each business unit. This research method is descriptive qualitative. Synergize the old system that already exists in the management of MSMEs with profit sharing based on the mato system using the focus group discussion method. The concept of profit sharing based on the existing mato system is currently used in most Padang restaurant management. Although RMP has turned into a large company, profit sharing based on the mato system has been used since its establishment, as a street vendor, as a micro-enterprise. In conclusion, the concept of profit sharing in the mato system can be injected into the management of MSMEs so that they can grow and develop faster. Keywords: Profit Sharing, Focus Group Discussion, MSME Management, Binary Opposition Synergy, Automatic System